The Scruffy Scruffy Dog - Todd, H E (Hodder and Stoughton Children Books, 1983)
The dogs of the village make an arrangement that each of them should win one prize at the local dog show. unfortunately, the only events left for scruffy to win is the most obedient Dog.
Keywords: Juvenile Fiction-Book